Arabidopsis MLO2 is a negative regulator of sensitivity to extracellular reactive oxygen species. (22nd February 2018) - Cui, Fuqiang; Wu, Hongpo; Safronov, Omid; Zhang, Panpan; Kumar, Rajeev; Kollist, Hannes; Salojärvi, Jarkko; Panstruga, Ralph; Overmyer, Kirk
Abstract: The atmospheric pollutant ozone (O3 ) is a strong oxidant that causes extracellular reactive oxygen species (ROS) formation, has significant ecological relevance, and is used here as a non‐invasive ROS inducer to study plant signalling. Previous genetic screens identified several mutants exhibiting enhanced O3 sensitivity, but few with enhanced tolerance. We found that loss‐of‐function mutants in Arabidopsis MLO2, a gene implicated in susceptibility to powdery mildew disease, exhibit enhanced dose‐dependent tolerance to O3 and extracellular ROS, but a normal response to intracellular ROS. This phenotype is increased in a mlo2 mlo6 mlo12 triple mutant, reminiscent of the genetic redundancy of MLO genes in powdery mildew resistance. Stomatal assays revealed that enhanced O3 tolerance in mlo2 mutants is not caused by altered stomatal conductance. We explored modulation of the mlo2 ‐associated O3 tolerance, powdery mildew resistance, and early senescence phenotypes by genetic epistasis analysis, involving mutants with known effects on ROS sensitivity or antifungal defence. Mining of publicly accessible microarray data suggests that these MLO proteins regulate accumulation of abiotic stress response transcripts, and transcript accumulation of MLO2 itself is O3 responsive. In summary, our data reveal MLO2 as a novel negative regulator in plant ROS responses, which links biotic and abiotic stress response pathways. Abstract : Arabidopsis MLO2 regulates several processes related to reactive oxygen species (ROS) signalling, including broad‐spectrum resistance to powdery mildew, leaf senescence, and callose deposition, prompting us to explore its relationship to ROS signalling using a genetic approach with exposure to the atmospheric pollutant ozone to induce extracellular ROS formation. MLO2 was found to act with unequal genetic redundancy with MLO6 and MLO12 in the negative regulation of sensitivity to extracellular, but not chloroplast‐derived, ROS. Genetic epistasis studies defined loci required for the mlo2 mutant's ROS, premature senescence, and immunity phenotypes, which could be genetically uncoupled. Meta‐analysis of MLO2 regulated genes revealed that MLO2 regulates genes related to ROS signalling and abiotic stress response, suggesting MLO2 may be a node integrating ROS, biotic, and abiotic stress signalling.